From Villainess to Gilead’s Nemesis: The (Un)easy Rehabilitation of Aunt Lydia - Ewelina Feldman-Kołodziejuk (Canada and Beyond)
The article takes under scrutiny the evolution of the key antagonist from Margaret Atwood’s The Handmaid’s Tale, namely, Aunt Lydia. In the sequel to her most popular novel, that is, The Testaments, the author boldly rewrote the villainous Aunt as Gilead’s undercover agent, forcing the reader to reconsider their own perception and reception of this character retrospectively. Predictably, many critics and fans found the said transformation implausible. Taking The Testaments as a point of departure, the article rereads the original tale, which, astonishingly, discloses a number of equivocal passages that in fact might provide credibility to Atwood’s audacious refashioning of Aunt Lydia as a Mayday spy. The article offers a reevaluation of Aunt Lydia’s villainy in The Handmaid’s Tale through the lens of her undercover identity, revealed in The Testaments. Firstly, it dissects the techniques and ploys the author used in the sequel to breed readers’ empathy for hitherto despised Aunt Lydia. It focuses on the overlap between the transformation of her character and the shift from the original novel’s criticism of second wave feminism towards the sequel’s embrace of the fourth wave. Finally, and most importantly, it discusses a selection of equivocal fragments from The Handmaid’s Tale that specifically pertain to Aunt Lydia.